4 u v tan x 0 5 u v cot x sin x 6 dividing

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ￿ sin x = 0 (3) −u￿ sin x + v ￿ cos x = sin2 x. (4) u￿ + v ￿ tan x = 0 (5) −u￿ + v ￿ cot x = sin x, (6) Dividing (3) by cos x and (4) by sin x yields and adding these yields v ￿ (tan x + cot x) = sin x. ￿ ￿ Multiplying through by tan x, we obtain v ￿ tan2 x + 1 = sin x tan x, i.e. v ￿ (sec2 x) = sin2 x sec x, so v ￿ = sin2 x cos x. Integrating, we have v= 13 sin x. 3 ￿ ￿ Now, from (5) we know that u￿ = −v ￿ tan x = − sin2 x cos x tan x = − sin3 x. Therefore ￿ u = − sin3 xdx AMATH 350 Assignment #5 Solutions - Fall 2011 Page 2 ￿ ￿ ￿ = − sin x sin2 x dx ￿ ￿ ￿ = − sin x 1 − cos2 x dx ￿ ￿ = − sin xdx + sin x cos2 xdx = cos x − 1 cos3 x. 3 We conclude that 1 1 cos4 x + sin4 x. 3 3 dy d2 y ￿2 ￿￿ ￿ (1) 5.This can 5x simplified: sin4 0 −cos4 x = sin x + cos2 x sin2 x − cos2 x = x2 2 + be + 5y = 0, x > x dx dx dy d2 y Therefore 0 > (1) 5.sin2 x2− cos2ln(.x),y x > ,0.xApply chain rule: x2 Let z x x+ 5 = 0 (a) + 5 = yp = cos2 x − 2. dx dx dy dz rule: 1 dy 1 dy dy...
View Full Document

Ask a homework question - tutors are online